2019
DOI: 10.7554/elife.46202
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and etiologic inferences of childhood pneumonia and diarrhea mortality in India

Abstract: Control of pneumonia and diarrhea mortality in India requires understanding of their etiologies. We combined time series analysis of seasonality, climate region, and clinical syndromes from 243,000 verbal autopsies in the nationally representative Million Death Study. Pneumonia mortality at 1 month-14 years was greatest in January (Rate ratio (RR) 1.66, 99% CI 1.51–1.82; versus the April minimum). Higher RRs at 1–11 months suggested respiratory syncytial virus (RSV) etiology. India’s humid subtropical region e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…These infectious diseases vary seasonally. Farrar et al (2019) find that diarrheal mortality is highest in the summer and monsoon months in India. On the other hand, pneumonia mortality is highest in the winter months.…”
Section: Seasonal Variation In Infant Mortality In India 1 Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…These infectious diseases vary seasonally. Farrar et al (2019) find that diarrheal mortality is highest in the summer and monsoon months in India. On the other hand, pneumonia mortality is highest in the winter months.…”
Section: Seasonal Variation In Infant Mortality In India 1 Introductionmentioning
confidence: 88%
“…Studies on seasonal variation in child health, particularly those examining month of birth effects on height-for-age deficits using the Demographic and Health Surveys (Lokshin and Radyakin, 2012) have been limited by data quality concerns (Larsen et al, 2019) and methodological issues (Agarwal et al, 2017;Cummins, 2015). In contrast to these studies of month-of-birth effects on height-for-age, studies examining seasonal variation in child mortality using sample registration (Farrar et al, 2019;Burkart et al, 2011) or surveillance site data (Muhuri, 1996;Kampe et al, 2015;Delaunay et al, 2001) have found clearer evidence of seasonal influences. As a contribution to resolving this puzzle in the literature on seasonal variation in child health in developing countries, I estimate period mortality rates between the ages 0 and 1 ( 1 m 0 ) by calendar month using Demographic and Health Survey (DHS) data for India.…”
Section: Seasonal Variation In Infant Mortality In India 1 Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…We obtained weather data local to each site’s health centers during the GEMS study using NOAA’s Integrated Surface Database ( Smith et al, 2011 ). The incidence of many pathogens, including rotavirus ( Cook et al, 1990 ), norovirus ( Ahmed et al, 2013 ), cholera ( Emch et al, 2008 ), and Salmonella ( Mohanty et al, 2006 ), are known to have seasonal patterns, and other analyses have established climatic factors to be associated with diarrheal diseases ( Colwell, 1996 , Chao et al, 2019 , Farrar et al, 2019 ). Stations near GEMS sites such as in The Gambia exhibit seasonal patterns ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%